A comparative study on the impact of the carbon nanotubes-modified polydimethylsiloxane nanocomposites on the colonization dynamics of the pioneer biofilm communities. (April 2018) - Sun, Yuan; Ji, Yubin; Lang, Yanhe; Wang, Lei; Liu, Bing; Zhang, Zhizhou
Abstract: In the current study, the AF properties of carbon nanotubes (CNTs)-modified polydimethylsiloxane (PDMS) nanocomposites were examined via the field assays. The impact of the CNTs incorporated in PDMS on the biological colonization and successional dynamics of the pioneer natural biofilm communities was investigated using the single-stranded conformation polymorphism (SSCP) technique. Coating characterizations, including water contact angle (WCA) measurement, scanning electron microscope (SEM) and atomic force microscopy (AFM) analysis were conducted in order to characterize the surface properties changes triggered by the incorporation of the CNT fillers. The results revealed that the incorporation of low amount of the CNT nanoparticles (0.1% wt) as fillers in the PDMS would greatly improve its AF properties under static submergence. The CNTs incorporated in the PDMS could exert significant impact on the diversity level, distribution patterns and the successional dynamics of the pioneer prokaryotic and eukaryotic microbial communities, particularly on the early eukaryotic microbial communities. Coating characterizations revealed the remarkable changes in the wettability and surface nanostructures of the PDMS resin would contribute considerably to the enhanced modulating and perturbation effects on the initial colonization of the pioneer microorganisms in the natural biofilms. Highlights: The anti-biofouling capacity of CNTs-modified PDMS nanocomposites were examined in the field assays. CNTs incorporated in PDMS resin can greatly impact the dynamics of the natural biofilm communities. The wettability and surface nanostructures were significantly affected with 0.1 (w/w) CNT nanoparticles incorporation. The surface wettability and nanostructure changes may contribute to the enhanced perturbations on the biofilm communities.